Intersatellite communication study for low earth orbit satellite network - Sun, Yuyao (Nanyang Technological University, 2023)
Due to the fast evolution of communication technologies, satellite communication is now an integral part of people's everyday life. It is an increasingly important area since the demand for the new generation of communication services is growing in a daily basis. Terahertz band is attracting considerable critical attention because of the many outstanding features terahertz wave has and it is considered as the key to satisfy the ever-increasing need. This work gives a brief review of the fundamental knowledge of satellite communication and Terahertz. The feasibility and performance of using terahertz band for intersatellite communication is studied in this work. The parameters configuration is discussed to take factors that affect the transmission of terahertz waves into consideration. Eight scenarios are designed and simulated. The results obtained are analyzed and compared so that conclusion are drawn. Problems and challenges which are obstacles to implementation of terahertz-based intersatellite communication including pointing accuracy and link maintenance are identified lastly.